COMPARATIVE AND COMPETITIVE ADVANTAGES ANALYSIS OF SHALLOT FARMING IN NORTH LAMPUNG REGENCY: A POLICY ANALYSIS MATRIX - Lestari, Sri Puji; Handayani, Sri; Ariska, Feby Musti; Hidayat, Rizky (Agric, 2025)
The shallot development initiative by the North Lampung Regency administration aims to enhance the welfare of vegetable producers and satisfy local shallot demand. The evolution of a commodity is affected by its input and output prices, which in turn impact the profits earned by farmers. The government's policies influence the input and output pricing for farmers. Shallots, as an emerging product in North Lampung Regency, require analysis to ascertain their potential financial and economic benefits, which indicate the competitiveness of shallots in the region. This research aims to evaluate the competitiveness of shallots by examining comparative and competitive advantages, as well as the influence of government policies on their competitiveness in North Lampung Regency. The employed analytical instrument is the Policy Analysis Matrix (PAM) approach. The cultivation of shallots in Lampung Utara Regency exhibits strong competitiveness on both competitive and comparative advantages. Consequently, the cultivation of shallots in Lampung Utara Regency merits advancement. Government measures, exemplified by input subsidies like fertilizer subsidies, can incentivize farmers by lowering the production costs associated with shallot cultivation. There is a necessity for output strategies that bolster shallot cultivation in North Lampung Regency, namely ensuring market certainty for shallot commodities and maintaining stable, equitable prices for shallots. Furthermore, farmers require information and direction on shallot cultivation to produce superior shallot products. Diversifying products derived from shallot commodities can serve as a strategy to ensure market stability for shallot commodities.